Factors Regarding The Purchase Of Artificial Gold Ornaments In Ariyalur District - et. al., Dr. A. Megala, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
From the prehistoric era women of all ages-the young, the middle-aged and the old have a fascination to wear jewelries mostly of gold and silver jewelry. But, cost for gold and silver jewelries is pretty high and in some cases the costs have gone out of the affordability of the buyers. This fact has paved the way to the use of imitation gold jewelry-jewelries made of metal, glass, plastic, enamel, silver, artificial gold, artificial diamond, wood and more. Currently a large number of people are using these artificial gold ornaments to make them beautiful and present them attractively. This study tries to find out the awareness about the sources of awareness, brands of artificial gold ornaments, types of artificial gold ornaments and awareness level of consumers.